Diferensiasi Hisab Waktu Salat (Studi Kitab al-Khulashah al-Wafiyyah dan Kontemporer) - Ahmad Fadholi (University of Muhammadiyah Sumatera Utara, 2022)
The discussion on the reckoning of prayer times contained in the Khulashah book has its own characteristics. The initial calculation process for prayer times has referred to the triangular ball algorithm system. Besides, there are also daqoiqut tamkin corrections presented through tables, and calculation methods using calculators. This study uses a library research paradigm with a qualitative theory verification approach using an arithmetic approach and the results are presented descriptively, then compared with similar methods. The results show that the coordinate transformation has referred to the modern astronomical system and the calculation system has used spherical trigonometry (spherical triangle). The calculation results have differences ranging from 0 to 3 minutes with contemporary methods. It is caused by differences in data and methods. If the calculation using the contemporary method there is a difference of 0 seconds to 12 seconds, this indicates that when the calculation is made modifications to the contemporary calculation system will produce a more accurate calculation